Strelkowella urunbasiensis gen. et sp. n. (Suctoria, Allantosomatidae) from the Hindgut of the Yakut Horse - Kornilova, O.A. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2004)
Обнаружена новая суктория семейства Allantosomatidae в содержимом кишечника якутской лошади. Предложен новый род Strelkowella gen. n., так как в отличие от других аллантосомид, данная инфузория имеет актинофоры. Типовой вид — Strelkowella urunbasiensis sp. n., это аллантосомида, у которой щупальца расположены на 6 актинофорах (по 3 актинофора на обоих концах тела). Щупальца (обычно по 6) увенчивают конец каждого актинофора. Новая суктория часто обнаруживается прикрепленной к телу Cycloposthium ponomarevi и C. dentiferum (Ciliophora, Entodiniomorphida). The new suctorian species presumably belonging to the family Allantosomatidae was recognized in digesta-samples from Yakut horses. The ciliate has actinophores, thus the new genus Strelkowella gen. n. is created for it. Strelkowella urunbasiensis sp. n. (type species of the genus) is the allantosomid with tentacles crowning, 6 actinophores (three actinophores on each end of the body). Commonly 6 equal capitate tentacles encircle the end of each actinophore. This new species was often observed adhered to the body of Cycloposthium ponomarevi and C. dentiferum (Ciliophora, Entodiniomorphida).